Substituent Effects on Carbonyl Stretching Frequencies in Substituted Styryl-2-Naphthyl Ketones - Thirunarayanan, G.; Ananthakrishna Nadar, P. (Asian Journal of Chemistry, 2010)
Some substituted styryl-2-naphthyl ketones were prepared and their carbonyl stretching frequencies (cm–1) were recorded and assigned from IR (KBr, 4000–400 cm–1) spectra. These data are correlated with Hammett parameter using single and multi-correlations with F and R functions. From the statistical analysis results the substituent effects on carbonyl group are predicted.